Good Corporate Governance in the Public Service Agency (Case Study at University of Brawijaya Malang) - Anggriawan, Ferry Fambia; kholis, Nur (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study was encouraged by one of the country's financial reform agenda, i.e. a shift from the traditional budgeting into a performance-based budgeting. By using the  performance-based  budgeting  system,  the use of  government funds  are no longer  only  the input-oriented,  but  rather the  performance. The reform includes the  implementation of good governance  in every aspect of Government in Indonesia.  In order to implement  Good  Governance  at  State Universities,  the government established the Public Service Agency with the aim of improving the quality of higher education services to the public. The purpose of this study was to determine the application of the principles of Good Governance at the University of Brawijaya Malang. This  research is a qualitative case study. The Method that used to collect  data was the documentation or archival, interviews, and observations. The results revealed that  the principles of Good Governance at  the University of Brawijaya Malang has been well  implementation. However,  there are several obstacles in its the implementation, i.e. the management of Universitas Brawijaya  less well, a lack of understanding about characteristic GCG itself, and some people still think that application of GCG it is less important. Keywords: Good Corporate Governance,  Country's Financial  Reform, Public Service Agency, State Universities